Detection of differentially methylated regions of irradiated fig tree selections - Fontanetti Rodrigues, Maria Gabriela [UNESP] (2017)
Fig tree (Ficus carica L.) breeding programs using conventional methods, such as directed crosses, to obtain new cultivars, are unworkable in many countries, including Brazil. Consequently, genetic breeding through mutagenesis has emerged as an important line of research that can improve this crop, and be a significant source of information about this species and assist in the implementation of propagation projects and appropriate management. The aim of this study was to verify the existence of epigenetic variability attributable to DNA methylation in irradiated fig selections when compared both to each other and to the main commercial cultivar, Roxo-de-Valinhos, which had previously used methylation-sensitive amplified polymorphism (MSAP) and DNA sequencing to detect the position of polymorphic regions, analyzable by bioinformatic tools. The sequencing of DNA, isolated from the differentially methylated sites, makes it possible to observe different patterns of methylation by sequencing the treated DNA with sodium bisulfite in the coding regions of regulatory genes active in the development, and fruit ripening stages. Furthermore, they have been found in the mitochondrial DNA of treatments which regulate the supply of energy in Adenosine triphosphate (ATP) form in plants. Closely related to their development, they justify the different phenotypes found in both fruit and plant growth that have suffered stress due to exposure to gamma radiation. Thus, future studies on gene expression in treatments have emerged as an extremely important strategy for understanding these complex regulatory systems, which may lead to the identification of genes of agricultural interest for the fig tree crop, and allow for manipulation and subsequent propagation of improved crops for commercial purposes.